Allergies in Germany – prevalence and perception by the public. (6th March 2013) - Augustin, Matthias; Franzke, Nadine; Beikert, Florian C.; Stadler, Rudolf; Reusch, Michael; Schmitt, Jochen; Schäfer, Ines
Summary Background During the recent decades allergies have become more frequent all over the world. However, it is unclear how important the topic of allergies is for the general German population and how appropriately patients with allergies are treated. Patients and methods A telephone survey was performed on a representative random sample of n = 1, 004 adults in Germany. The survey was performed by the Forsa Institute for Social Research and Statistical Analysis, Berlin, Germany, in the period from 31 January to 2 February 2012. Results Of the interviewees 52% responded that the topic of allergies concerned them; in 33% actually an allergy had been diagnosed by a physician. The proportion of allergies in the population correlated with the level of school education and was higher among people with a higher educational status. No differences in allergy rates were found between Eastern and Western Germany. Among allergic persons, 53% reported to be burdened by their allergy, 48% suffered from impaired performance because of their allergic symptoms. Among people suffering from pollen allergy, only 28% received sublingual immune therapy, with which 70% were satisfied. While 58% practiced self‐medication, only 21% of the allergic persons were treated with anti‐allergic drugs during their allergy flares. Conclusions Allergic diseases are a common, often burdensome problem in the German population, but nevertheless the medical treatment of people affected is still insufficient. The proportion of patients receiving sublingual immune therapy as causal treatment is comparatively low. Active steps are needed to improve the utilization behavior of patients, e. g. to take advice of an allergy specialist.